Organicist Perspectives in Newly Published Biology Textbooks - Sonnenschein, Carlos (Organisms. Journal of Biological Sciences, 2024)
Review of Bernd Rosslenbroich (2023). Propertiesof Life: Toward a Theory of Organismic Biology. Vienna Series in Theoretical Biology. Boston: The MIT Press.